Rhabdomyomatous carcinoma of the thymus - Moreira de Queiroga, Eduardo [UNESP]; Chikota, Horacio; Bacchi, Carlos E. [UNESP]; Moran, Cesar A.; Suster, Saul (Wolters Kluwer, 2004)
Myoid cells have been described in the thymus in association with a variety of benign and malignant conditions. The presence of a benign rhabdomyomatous component in a malignant primary thymic epithelial neoplasm, however, is extremely rare. A case of poorly differentiated carcinoma of the thymus arising in the posterior mediastinum containing a prominent rhabdomyomatous component is described. The patient, a 70-year-old woman, was seen for a large posterior mediastinal mass. An open chest biopsy revealed an extensively necrotic tumor composed of islands of atypical cells with vesicular nuclei and prominent nucleoli with numerous mitotic figures admixed with abortive glandular structures. Interspersed with the malignant epithelial components were islands of large cells containing brightly eosinophilic cytoplasm and small, round, excentrically placed nuclei. Immunohistochemical studies showed strong positivity of the epithelial cells for cytokeratin and strong positivity of the myoid cells for pan-actin, desmin, and myogenin. The possible relationship of the rhabdomyomatous component of this tumor with the myoid cells of the thymus is discussed.
Keywords: Myoid cells; Rhabdomyosarcoma; Thymic carcinoma; cytokeratin; desmin; myogenin; aged; autopsy; biopsy; bone marrow cell; case report; cell differentiation; cell structure; epithelium cell; female; histopathology; human; human tissue; immunohistochemistry; mediastinum mass; mitosis; necrosis; rhabdomyosarcoma; thymus cancer; Aged; Female; Humans; Rhabdomyoma; Thymus Neoplasms